2019
DOI: 10.1038/s41598-019-53683-4
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of gaze during action preparation under threat imminence

Abstract: When confronted with threatening stimuli, animals typically respond with freezing behavior characterized by reduced movement and heart rate deceleration. Freezing-like responses during threat anticipation have also been observed in humans and are associated with anxiety. Recent evidence yet suggests that freezing does not necessarily reflect helpless immobility but can also aid the preparation of a threat escape. To investigate which further behavioral responses human freezing encompasses, we presented 50 youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
87
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(112 citation statements)
references
References 50 publications
16
87
2
Order By: Relevance
“…Lesioning the CeA, a region critically implicated in the freezing response increased active avoidance in those animals (Choi and Kim, 2010;Lázaro-Muñoz et al, 2010). In contrast, human studies show that freezing facilitates rapid responding (Jennings and van der Molen, 2005;del Paso et al, 2015;Gladwin et al, 2016;Hashemi et al, 2019a,b;Ribeiro and Castelo-Branco, 2019;Rösler and Gamer, 2019) and one study showed that threatanticipatory freezing responses biased subsequent instrumental actions toward faster threat avoidance (Ly et al, 2014). Two recent studies (Hashemi et al, 2019a,b) manipulated threat of shock by using a task in which an avatar would shoot if an incorrect or delayed response was made.…”
Section: Threat-anticipatory Freezing Is Associated With Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…Lesioning the CeA, a region critically implicated in the freezing response increased active avoidance in those animals (Choi and Kim, 2010;Lázaro-Muñoz et al, 2010). In contrast, human studies show that freezing facilitates rapid responding (Jennings and van der Molen, 2005;del Paso et al, 2015;Gladwin et al, 2016;Hashemi et al, 2019a,b;Ribeiro and Castelo-Branco, 2019;Rösler and Gamer, 2019) and one study showed that threatanticipatory freezing responses biased subsequent instrumental actions toward faster threat avoidance (Ly et al, 2014). Two recent studies (Hashemi et al, 2019a,b) manipulated threat of shock by using a task in which an avatar would shoot if an incorrect or delayed response was made.…”
Section: Threat-anticipatory Freezing Is Associated With Informationmentioning
confidence: 99%
“…Evidence for the involvement of freezing in information gathering comes from studies in humans showing that the magnitude of the freezing-related bradycardia is associated with changes in perception. For example, stronger freezing responses have been associated with preferential processing of low over high spatial frequency features of a visual stimulus (Lojowska et al, 2015(Lojowska et al, , 2018 and reduced visual exploration of non-threat-relevant stimulus features (Rösler and Gamer, 2019).…”
Section: Threat-anticipatory Freezing Is Associated With Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Differential effects of US vs. neutral stimuli on heart rate were observed, and the data reflected awareness of the purported CS+ vs. CS-. As the task was simple and no behavioral responses were required, these cardiac responses were likely elicited by these stimuli, unconfounded by task difficulty (Richter, 2010;Fairclough and Ewing, 2017) or action/action preparation (Cooke et al, 2014;Rösler and Gamer, 2019). The data offer new information on adult human responses to appetitive stimuli and cues that predict them.…”
Section: Discussionmentioning
confidence: 92%